Two Interpretations of Narcissus in Psychoanalytical Context - Jekentaitė, Leonarda (Problemos, 2002)
An article is concerned with some ethical and aesthetical insights in the latest modifications of psychoanalysis. French psychoanalyst and philosopher J. Lacan had found a very fruitful way of interpretations, applying concepts of modern language philosophy. The main objective of deconstruction is radical reinterpretation of reality, seeking to restore an uninterrupted continuity of sense as ethically coloured totality of personal consciousness. Psychoanalytically orientated sociologist H. Marcuse thought, that beauty and art in reality would have to remind us the programme of Eros - our natural strivings for freedom and happiness, - while the life reality is enslaving us in the chains of dehumanizing work and consume. The mythical hero Narcisus can be condemned ethically and justified aesthetically at the same time. In extreme expierence it is difficult to differentiate madness, ammoralism or self-sacrificing passion of creator.
Keywords: psychoanalysis; J. Lacan; H. Marcuse; ethics; aesthetics